Big answers from small worlds: a user's guide for protist microcosms as a model system in ecology and evolution. Issue 2 (15th December 2014) - Altermatt, Florian; Fronhofer, Emanuel A.; Garnier, Aurélie; Giometto, Andrea; Hammes, Frederik; Klecka, Jan; Legrand, Delphine; Mächler, Elvira; Massie, Thomas M.; Pennekamp, Frank; Plebani, Marco; Pontarp, Mikael; et al.
Summary: Laboratory microcosm experiments using protists as model organisms have a long tradition and are widely used to investigate general concepts in population biology, community ecology and evolutionary biology. Many variables of interest are measured in order to study processes and patterns at different spatiotemporal scales and across all levels of biological organization. This includes measurements of body size, mobility or abundance, in order to understand population dynamics, dispersal behaviour and ecosystem processes. Also, a variety of manipulations are employed, such as temperature changes or varying connectivity in spatial microcosm networks. Past studies, however, have used varying methods for maintenance, measurement, and manipulation, which hinders across‐study comparisons and meta‐analyses, and the added value they bring. Furthermore, application of techniques such as flow cytometry, image and video analyses, and in situ environmental probes provide novel and improved opportunities to quantify variables of interest at unprecedented precision and temporal resolution. Here, we take the first step towards a standardization of well‐established and novel methods and techniques within the field of protist microcosm experiments. We provide a comprehensive overview of maintenance, measurement and manipulation methods. An extensive supplement contains detailed protocols of all methods, and these protocols also exist in a community updateable online repository. We envision that such a synthesis and standardization of methods will overcome shortcomings and challenges faced by past studies and also promote activities such as meta‐analyses and distributed experiments conducted simultaneously across many different laboratories at a global scale.